2015
DOI: 10.1159/000369091
|View full text |Cite
|
Sign up to set email alerts
|

The Subventricular Zone in the Immature Piglet Brain: Anatomy and Exodus of Neuroblasts into White Matter after Traumatic Brain Injury

Abstract: Stimulation of postnatal neurogenesis in the subventricular zone (SVZ) and robust migration of neuroblasts to the lesion site in response to traumatic brain injury (TBI) is well established in rodent species; however, it is not yet known whether postnatal neurogenesis plays a role in repair after TBI in gyrencephalic species. Here we describe the anatomy of the SVZ in the piglet for the first time and initiate an investigation into the effect of TBI on the SVZ architecture and the number of neuroblasts in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…This age-related difference in the degree of injury-induced endogenous cell response has also been recently reported in species with gyrencephalic brains. In this study, Costine and colleagues have found that in a cortical impact injury piglet model, TBI significantly increased cell proliferation in the SVZ in piglets that were injured at post-natal day 7 but not in animals injured at 4 months old (Costine et al, 2015). Furthermore, we and others have found that injury-induced newly generated granular cells integrate into the existing hippocampal circuitry (Emery et al, 2005; Sun et al, 2007), and this endogenous neurogenesis is directly associated with the innate cognitive recovery observed following injury (Blaiss et al, 2011; Sun et al, 2015).…”
Section: Tbi-induced Neurogenesis In Experimental Studies In Tbi Animmentioning
confidence: 67%
“…This age-related difference in the degree of injury-induced endogenous cell response has also been recently reported in species with gyrencephalic brains. In this study, Costine and colleagues have found that in a cortical impact injury piglet model, TBI significantly increased cell proliferation in the SVZ in piglets that were injured at post-natal day 7 but not in animals injured at 4 months old (Costine et al, 2015). Furthermore, we and others have found that injury-induced newly generated granular cells integrate into the existing hippocampal circuitry (Emery et al, 2005; Sun et al, 2007), and this endogenous neurogenesis is directly associated with the innate cognitive recovery observed following injury (Blaiss et al, 2011; Sun et al, 2015).…”
Section: Tbi-induced Neurogenesis In Experimental Studies In Tbi Animmentioning
confidence: 67%
“…Piglets received a total of 4 injections (Table 1); BrdU (50 mg/kg; IP) or vehicle (saline) was administered as previously described while piglets were lightly anesthetized with isoflurane once per day (Costine et al, 2015). The different time points in administration of BrdU was to compare the number of BrdU + neurons before relative to after injury, in order to identify whether injury itself stimulated the formation of new neurons from the SVZ within the first days after trauma.…”
Section: Methodsmentioning
confidence: 99%
“…In normal early postnatal development in gyrencephalic species, large populations of neuroblasts are found in a migratory morphology in the major white matter tracts (Sanai et al, 2011; Costine et al, 2015). The SVZ generates neuroblasts that migrate to distant brain regions via distinct pathways, migratory streams to the olfactory bulbs (where population continues past infancy), prefrontal cortex, and possibly the nucleus accumbens (De Marchis et al, 2004; Sanai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Male, Yorkshire piglets (Earle Parsons & Sons, Inc., Hadley, MA) were housed and fed as previously described after arrival at post-natal day (PND) 5, 19, or 28. 25 Milk replacer (PND 5) or grain pellets (PND 19 and 28) were removed the evening prior to surgery and piglets were given a liquid electrolyte solution (BlueLite; TechMix, Inc., Stewart, MN). A total of 48 piglets (Experimental Phase 1, n = 8; Experimental Phase 2, n = 25; Experimental Phase 3, n = 15) were used to develop this model in three experimental phases.…”
Section: Protocols General To All Experimental Phasesmentioning
confidence: 99%
“…23,25 The brain was removed leaving the ventral dura intact and post-fixed at 4°C for up to 1 month. The eyes with attached optic nerves were removed by dissection through the floor of the anterior cranial fossa into the orbital space to expose the globe and contents of the orbit in a subset of injured piglets (n = 3).…”
Section: Protocol Specific To Experimental Phasementioning
confidence: 99%